ANALYSIS OF STUDENT MISCONCEPTIONS ON THE MOLE CONCEPT MATERIAL USING A THREE TIER DIAGNOSTIC TEST INSTRUMENT - Sembiring, Erika Fortuna Sagita; Roza, Destria (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
These misconceptions can occur due to students' low understanding of basic mathematics which is sustainable in the previous school. This study aims to determine the percentage of students' misconception level through the Three-Tier test instrument on the mole concept material of class X at SMAN 18 Medan. Data collection techniques were carried out by conducting interviews and observations to teachers and distributing written tests in the form of three-tier diagnostic tests consisting of 25 multiple choice questions. The data that has been obtained shows that there are misconceptions in class X students in the material of mole concept. The results of this study showed that Class X students of SMA NEGERI 18 MEDAN had 53.41% misconceptions, 34.94% understood the concept, and 11.65% didn’t understand the concept.